Antiviral options and therapeutics against influenza: history, latest developments and future prospects - Meseko, Clement; Sanicas, Melvin; Asha, Kumari; Sulaiman, Lanre; Kumar, Binod (Frontiers in Cellular and Infection Microbiology, 2023)
Drugs and chemotherapeutics have helped to manage devastating impacts of infectious diseases since the concept of ‘magic bullet’. The World Health Organization estimates about 650,000 deaths due to respiratory diseases linked to seasonal influenza each year. Pandemic influenza, on the other hand, is the most feared health disaster and probably would have greater and immediate impact on humanity than climate change. While countermeasures, biosecurity and vaccination remain the most effective preventive strategies against this highly infectious and communicable disease, antivirals are nonetheless essential to mitigate clinical manifestations following infection and to reduce devastating complications and mortality. Continuous emergence of the novel strains of rapidly evolving influenza viruses, some of which are intractable, require new approaches towards influenza chemotherapeutics including optimization of existing anti-infectives and search for novel therapies. Effective management of influenza infections depend on the safety and efficacy of selected anti-infective in-vitro studies and their clinical applications. The outcomes of therapies are also dependent on understanding diversity in patient groups, co-morbidities, co-infections and combination therapies. In this extensive review, we have discussed the challenges of influenza epidemics and pandemics and discoursed the options for anti-viral chemotherapies for effective management of influenza virus infections.